2021
DOI: 10.3390/f12101311
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Habitat Conditions on the Properties of Pinewood

Abstract: This article starts a series of articles on dependences between the conditions of the growth of trees in forests and the technical aspects and directions of using the raw material obtained from these trees. This is a key feature for wood purchasers because it determines the efficiency of production and directly affects the final financial result of their activity. Wood represents an environmentally sustainable and renewable material, which is a widely available raw material on the market and must meet specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…This study found no significant difference in the fresh wood root biomass density to the soil slope class and position in both tree species. Wood density is influenced by the following several factors: the species of the tree [68], ages [69], the growth conditions of the soil [70], topography [71,72], and inter-tree competition [73]. According to Mahajan [74], the density of wood depends on the weight of water in a given volume of wood, the weight of the wood substance in a given volume of wood, and the volume of wood at a specified moisture content.…”
Section: Physical Properties Of Woody Root Biomassmentioning
confidence: 99%
“…This study found no significant difference in the fresh wood root biomass density to the soil slope class and position in both tree species. Wood density is influenced by the following several factors: the species of the tree [68], ages [69], the growth conditions of the soil [70], topography [71,72], and inter-tree competition [73]. According to Mahajan [74], the density of wood depends on the weight of water in a given volume of wood, the weight of the wood substance in a given volume of wood, and the volume of wood at a specified moisture content.…”
Section: Physical Properties Of Woody Root Biomassmentioning
confidence: 99%
“…It can form completely different forests -from highly productive oxalis pine forests to sparse dry lichen and waterlogged sphagnum forests [25,26]. Under different conditions, growth processes vary significantly, affecting the trees' morphological characteristics and wood properties [27][28][29][30][31][32]. It is known that, in other woody species, heartwood formation is controlled by diverse environmental conditions and soil fertility [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
“…correlation of tissues are a necessary prerequisite for a tree to adapt to changing environmental conditions (Pazdrowski and Spława-Neyman 1996, Korchagov and Gribov 2009, Eremin and Chavchavadze 2015, Zaytsev et al 2020, Wieruszewski and Mydlarz 2021. It is obvious that the choice of a growth strategy by a particular tree and changes in its wood structure can be conditioned by the deficit of organic matter and, as a consequence, by the need to place a certain number of water-conducting elements on a smaller area (Arseneva andChavchavadze 2001, Romanovsky andShchekalev 2014).…”
mentioning
confidence: 99%
“…In scholarly literature there is a large volume of publications that allow us to judge the influence of site conditions on the variation of volumetric and technical parameters of pine wood (Melekhov 1949, Vikhrov 1954, Ugolev 2001, Danilov et al 2018, Schimleck et al 2018, Wieruszewski and Mydlarz 2021. Under conditions of longterm technogenic impact, Scots pine shows an increase in the share of latewood in the structure of annual growth in terms of diameter (Arseneva and Chavchavadze 2001, Shchekalev and Tarkhanov 2006, Yarmishko 2012.…”
mentioning
confidence: 99%
See 1 more Smart Citation